Pengembangan Sistem Layanan Pemesanan Lapangan Futsal dengan memanfaatkan Teknologi Payment Gateway (Studi Kasus: Marcella Futsal Jombang) - Muhammad Rizki Augusta; Widhy Hayuhardhika Nugraha Putra; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Futsal is one of a popular indoor sport in Indonesia. No wonder this is used by business people in Indonesia, by making a futsal field rental, one of which is Marcella Futsal Jombang. However, there are several problems that often happen. It often happens that there are two people reserve the futsal field at the same time, where Marcella Futsal only provides one futsal field. Then in reservation data storage still uses the manual method and there are also some customers who do not pay down payments when reserving the futsal field. Based on these problems, a system is needed to place reservation for the futsal field. This system was developed in the mobile application using the waterfall method. This system utilizes Midtrans payment gateway technology to make it easier for customers to make transactions when reserving a futsal field, either in paying down payments or paying rental fees. In addition, there is also a feature to view sports news obtained from the NewsAPI API. Then black box testing was carried out and get 100% results which show that the features provided by the system are functioning properly and in accordance with needs. Then in the usability testing using the System Usability Scale get the final value 85. Based on this value, it was found that the system was acceptable with a scale of B values, and very good at the level of system usability.